2012
DOI: 10.1090/s0002-9947-2011-05534-0
|View full text |Cite
|
Sign up to set email alerts
|

Sharp bounds for general commutators on weighted Lebesgue spaces

Abstract: Abstract. We show that if a linear operator T is bounded on weighted Lebesgue space L 2 (w) and obeys a linear bound with respect to the A 2 constant of the weight, then its commutator [b, T ] with a function b in BM O will obey a quadratic bound with respect to the A 2 constant of the weight. We also prove that the kth-order] will obey a bound that is a power (k + 1) of the A 2 constant of the weight. Sharp extrapolation provides corresponding L p (w) estimates. In particular these estimates hold for T any Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…It has been shown that the Calderón-Zgymund singular integral operator with smooth kernel [b, T ]f := bT (f )−T (bf ) is a bounded operator on L p , 1 < p < ∞, when b is a BMO function. Weighted estimates for the commutator have been studied in [1], [4], [6], [7], and elsewhere. Also [6] and [7] provide the sharp version of one weighted estimates for the commutators.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…It has been shown that the Calderón-Zgymund singular integral operator with smooth kernel [b, T ]f := bT (f )−T (bf ) is a bounded operator on L p , 1 < p < ∞, when b is a BMO function. Weighted estimates for the commutator have been studied in [1], [4], [6], [7], and elsewhere. Also [6] and [7] provide the sharp version of one weighted estimates for the commutators.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…A refinement of the argument in [11] shows that Theorem 15. If a linear operator T obeys a power bound in L r (w) for all w ∈ A r ,…”
Section: Transference Theorem In L R (W) For Commutatorsmentioning
confidence: 90%
“…Extrapolation gives bounds on L p (w), they are sharp for all 1 < p < ∞, all k ≥ 1 and all dimensions, as examples involving the Riesz transforms show [11].…”
Section: Transference Theorem In L R (W) For Commutatorsmentioning
confidence: 96%
See 2 more Smart Citations